Political Authority and European Community: The Challenge of the Christian Political Tradition - O'Donovan, Joan Lockwood (Scottish journal of theology, 1994)
Today the whole of Europe, East and West, is caught up in the search for new political and economic structures, sadly, along violent and atavistic as well as peaceful and constructive paths. In the West the fulcrum of change is the halting movement of countries toward economic and political ‘integration’ within the European Community. The issue of what form, or forms, the Community should take (whether federal, confederal, or more loosely associative) is understandably divisive, for its resolution will determine the political shape, not only of the member states, but also of those western European countries (should there be any eventually) that remain either outside the Community or only partially integrated in it. Moreover, it will decisively influence the political and economic aspirations and possibilities of the Community's eastern European neighbours, and even of their Soviet or ex-Soviet neighbours. Thus are we justified in viewing the fate of the European Community as the fate of Europe. Consequendy, it is a task of theoretical and practical moment to attempt to grasp the civilisational meaning of the projected European union with the help of some points of reference from western Europe's past and present.